Distributed Fixed-Time Optimization in Economic Dispatch Over Directed Networks - Dai, Hao; Jia, Jinping; Yan, Li; Fang, Xinpeng; Chen, Weisheng (IEEE transactions on industrial informatics, 2021)
A distributed algorithm is presented in this article under directed communication networks, which is used to solve the economic dispatch problem in fixed time in smart grid systems. A new globally fixed-time stability theory (Lemma 3 ) is first given in this article, which contains a new upper bound for the estimation of the settling time. Moreover, the fixed-time convergence for the proposed algorithm is rigorously proved with the aid of convex optimization theory, the new lemma, and Lyapunov stability theory under the strongly connected and weight-balanced network topology. Finally, numerical simulations show the effectiveness and advantages of the distributed fixed-time optimization algorithm.